Pravica do sodnega varstva po Paktu o migracijah - Šelih, Urh (Pravnik, 2026)
This article analyses the right to judicial protection in the context of the EU’s New Pact on Migration and Asylum, adopted in December 2023. While the Pact promises more effective and solidarity-based migration management, many provisions raise serious concerns about fundamental rights protection. Particularly worrying is the expanded use of border and accelerated procedures, which may lead to systematic detention and erosion of procedural safeguards. Access to legal aid remains fragmented and dependent on national regulations, threatening equal access to protection. Legal remedies often lack an automatic suspensive effect, meaning that applicants may be returned before their appeals are heard. The article warns that the Pact’s success will depend heavily on its implementation and the political will of Member States. Without proper enforcement, the new legal framework risks entrenching existing shortcomings and undermining the right to asylum within the EU
Keywords: access to justice; asylum; azil; begunci; EU law; Pact on Migration and Asylum; Pakt o migracijah in azilu; pravica do sodnega varstva; pravo EU